Biological macrofouling and electrochemical corrosion properties of structural steel AH36 in natural seawater at Hon Tre island, Nha Trang - Chi, Nguyen Van; Dong Van Kien,; Le Hong Quan,; Cao Nhat Linh,; Nong Quoc Quang,; Nguyen Duc Anh,; Pham Thi Hai Yen,; Le Quoc Hung, (Vietnam Journal of Science and Technology, 2022)
The biological macrofouling characteristics and electrochemical corrosion behavior of structural steel AH36 in natural seawater were studied continuously for 12 months at Hon Tre Island, Nha Trang – Vietnam. Electrochemical corrosion properties were studied using a PPGS-HHMC12 multi-channel device produced by the Institute of Chemistry, VAST. Tests were conducted at depths of 0.6 m, 1.8 m, and 3.0 m; under anti-macrofouling control, rotary movement, and under laboratory conditions as a comparison option.The results showed that macro-fouling formed and grew rapidly in both quantity, size and biomass in the next 3 months, then slowly and stably increased to about 8 months (6.06 kg.m-2). The OCP shifted to a positive potential, then reached a stable value of about -550 mV during the rest of exposure time. The corrosion current density decreased sharply from the first month to the fourth month, then reached a stable value of about 10 µA.cm-2 in next months of testing. The corrosion rate of AH36 steel in natural seawater in the field was higer than that under laboratory condition, which could be explained by the interaction of many factors such as dissolved oxygen, biofouling, water current, solar radiation